Complexities of Collaborative Crisis Response: Stakeholders’ Perception of Coordination Challenges during the Influx of Ukrainian Forced Migrants to Warsaw - Lyubashenko, Igor (Studia z Polityki Publicznej, 2024)
The article delves into the challenges of multi-sectoral coordination in emergency food relief for Ukrainian war refugees in Warsaw. Utilizing the COM-B model, we analyzed interviews with representatives from public authorities, the private sector, and NGOs to identify perceived barriers in capability, opportunity, and motivation affecting collaboration. Our findings indicate a consensus across sectors regarding capability and opportunity barriers. Key capability issues include coordination complexities, communication gaps, and unclear roles, leading to systemic inefficiencies and response delays. Opportunity barriers are predominantly linked to procedural and bureaucratic challenges, exacerbated by conflicting policies and cultural factors. Motivational challenges differ by sector, ranging from frustrations associated with attempts to collect high-quality donations in the public sector, operational risks and misuse concerns in the private sector, to morale decline due to criticism in NGOs.